Color of Karag Crackers with The Addition of Annatto Pigments and Variation of Types of Coatings - Isti Handayani; Nazmirafa Effendi (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
Annatto pigment has the potential to be used as a natural dye. The addition of coating material is expected to act as a carrier and binder of annatto seed pigment in karak crackers. This study aims to determine the effect of the addition of annatto seed pigment and the type of coating on the color of coral crackers. Pigment coating is carried out using starch and maltodextrin. As a comparison, the pigment is directly added to the cracker dough, and as a control karag cracker is made without the addition of pigment. Coated annatto seed pigment was added as a colorant to the karag cracker dough with various concentrations of 2, 3, and 4%. Using the Munsen color dictionary, the potential of coated pigments as coloring agents was observed by measuring the hue, value, and chroma of the karag crackers. The results showed that the hue of karag crackers with the addition of annatto pigment produced a red color and mostly yellow-orange (YR) while the control (without the addition of pigment) produced a yellow color with a Hue (color) value between 2.5 to 5YR except for starch coating with a concentration of pigment 2% produces a red color. The use of maltodextrin coatings resulted in a lower value (brightness) (4.89) than starch (5.44) and without coatings (5.33), but chroma (color density) was not affected by the type of coating with chroma values ​​ranging from 7.56 up to 8.44. Increasing the concentration of coated annatto pigment by 4% decreased the value of coral crackers, but the addition of both coated and uncoated annatto pigment concentrations was not able to increase chroma.